A kind of LED organic silicon encapsulation adhesive and preparation method thereof

By using small molecule vinyl silane and hydrogen-containing silicone oil to prepare LED silicone packaging glue, the problems of complex process, high cost and poor bonding performance in the prior art are solved, and efficient and low-cost packaging material preparation is achieved, and excellent performance is achieved.

CN115926734BActive Publication Date: 2025-04-25GUANGZHOU HUAXINKE ENTERPRISE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211631459.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-25
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The existing silicone packaging glue has complex production processes, high cost, large viscosity, poor adhesive performance, poor heat resistance, poor barrier performance and insufficient mechanical properties, resulting in poor vulcanization resistance, and high temperature and high humidity.

Method used

Small molecule vinyl silane and hydrogen-containing silicone oil are used as the main raw materials to prepare LED silicone packaging glue through a simple and low-cost process to improve cross-linking density and enhance hot and cold impact, anti-vulcanization, barrier, heat resistance and high temperature and high humidity performance.

Benefits of technology

It realizes low-cost, simple process and high cross-linking density LED packaging materials, with excellent anti-vulcanization properties, hot and cold impact properties, barrier properties, heat resistance and high temperature and high humidity properties, avoiding many defects of traditional rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004005947140000031
    Figure BDA0004005947140000031
  • Figure BDA0004005947140000032
    Figure BDA0004005947140000032
  • Figure BDA0004005947140000131
    Figure BDA0004005947140000131
Patent Text Reader

Abstract

The present invention discloses a LED organic silicon encapsulation adhesive and a preparation method thereof, and belongs to the technical field of polymer materials. The LED organic silicon encapsulation adhesive of the present invention comprises the following components: component A and component B, wherein the component A comprises the following components in parts by weight: 15-30 parts of polyvinyl cyclosilane and 0.0005-0.006 parts of platinum catalyst; the component B comprises the following components in parts by weight: 20-50 parts of silicon hydrogen crosslinking agent and 0.05-1 parts of inhibitor; the mixing ratio of the components A and B is: the molar ratio of the total amount of vinyl groups to the total amount of silicon hydrogen groups in the components A and B is 1: (1.2-1.5). The LED organic silicon encapsulation adhesive of the present invention has low viscosity, high crosslinking density, good cold and hot shock performance, anti-sulfurization performance, barrier performance, heat resistance and high temperature and high humidity performance. The preparation process of the present invention is simple, the curing reaction is fast, the cost is low, the production efficiency is high, and it has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an LED organic silicon encapsulation adhesive and a preparation method thereof. Background Art

[0002] LED is a semiconductor light-emitting device that can directly convert electrical energy into light energy. It has the advantages of simple structure, energy saving, long life, environmental protection, high luminous efficiency, bright colors, etc., and has become a new lighting technology. The performance of LED sealant has an important impact on the brightness, luminous efficiency and service life of LED devices. With the continuous advancement and improvement of LED technology, more stringent requirements are put forward for the performance of LED potting glue. Silicone LED packaging materials are more and more widely used due to their high refractive index, high light transmittance, and resistance to cold and hot shocks. Liquid silicone rubber is divided into two categories according to the packaging form: single-component and two-component, and can be divided into two series: condensation type and addition type according to the vulcanization mechanism. Most LED packages use two-component addition type liquid silicone rubber. Its main components are: vinyl-containing polyorganosiloxane base polymer, hydrogen-containing polyorganosiloxane crosslinking agent, platinum (Pt) complex catalyst and reinforcing filler. After the rubber compound is prepared, it is cross-linked and cured by hydrosilylation reaction at room temperature or under heating conditions to obtain silicone LED packaging material. It has the advantages of no by-products during the vulcanization process, low shrinkage and deep curing, and has been rapidly developed in the LED field.

[0003] At present, most silicone encapsulants are cured by addition using vinyl-containing polyorganosiloxane base polymers and hydrogen-containing polyorganosiloxane crosslinkers as the base resin. Vinyl and silane hydrogen groups are generally at the end of the molecular chain, or they can be on the side chain or both. The use of this traditional long-chain base resin with high functional group content brings obvious disadvantages:

[0004] (1) The production process is relatively complicated and the production efficiency is low. Whether it is the open-loop method or the hydrolysis method, volatile organic solvents are usually used, which causes environmental pollution and harms human health. Impurities are easily introduced and multiple washings are required to remove the catalyst. The residual impurities have an adverse effect on the application performance of the final product (sulfurization, temperature resistance, UV resistance, etc.).

[0005] (2) The modification of macromolecular base polymers is difficult and complicated in the actual production process. The cost is relatively high, and its application is greatly restricted and rarely used.

[0006] (3) The viscosity of the macromolecular matrix resin is high, which can easily cause dispensing bubbles and drawing.

[0007] In addition, since silicone rubber is a highly saturated non-polar rubber after vulcanization, the molecular surface energy is low, and thus the adhesion to the base material is low. In applications, it is easy to have poor adhesion between the addition-type silicone LED encapsulation glue and the encapsulation bracket, which allows moisture to invade through the interface between the two, resulting in poor airtightness, causing the encapsulated product to fail after hot and cold shock and high temperature and humidity tests. Generally, the adhesion between the silicone rubber and the substrate is improved by using a primer or modifying the base glue or adding a tackifier to the silicone rubber. However, the use of a primer increases the production process and production time, reduces production efficiency, and the volatilization of the primer solvent is prone to environmental pollution; the addition of a tackifier also has its fatal flaws. Considering the cost, the tackifier is generally a small molecule, which is easily thermally migrated, precipitated and sprayed, etc., resulting in tackification failure; in addition, the introduction of impurities or residual N, P, S, etc. in the tackifier will cause catalyst poisoning, deteriorating the vulcanization, processing and mechanical properties of silicone rubber.

[0008] The existing high-fold silicone encapsulation adhesives on the market have poor heat resistance, poor barrier properties, and inadequate mechanical properties, resulting in poor anti-vulcanization performance and easy failure of the lamp in high and low temperature and high temperature and humidity. The main reason is insufficient cross-linking density: the active functional groups on the long-chain base adhesive are easily wrapped by the molecular chains, resulting in incomplete reaction and low reaction activity; at the same time, the three-dimensional network formed after the long-chain base adhesive is cured has large gaps between molecules and low barrier properties. Although increasing the side chain active functional groups can increase the cross-linking density, it will reduce toughness, resulting in failure of the lamp in high and low temperature tests.

[0009] Therefore, it is of great significance to develop a LED packaging material with low cost, simple process, high cross-linking density, excellent anti-sulfurization performance, hot and cold shock, and high temperature and high humidity performance. Summary of the invention

[0010] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an LED silicone encapsulation adhesive and a preparation method thereof. The LED silicone encapsulation adhesive is prepared by using small molecule vinyl silane and hydrogen-containing silicone oil as main raw materials, and has a simple preparation process, low cost and no pollution. The prepared LED silicone encapsulation adhesive has a high cross-linking density and has good cold and hot shock performance, anti-sulfurization performance, barrier performance, heat resistance and high temperature and high humidity performance.

[0011] To achieve the above object, the technical solution adopted by the present invention is:

[0012] In a first aspect, the present invention provides an organic silicon encapsulation adhesive for LEDs, comprising the following components: component A and component B, wherein component A comprises the following components in parts by weight: 15-30 parts of polyvinyl cyclosilane and 0.0005-0.006 parts of a platinum catalyst;

[0013] The B component comprises the following components in parts by weight: 20-50 parts of a silane crosslinking agent and 0.05-1 part of an inhibitor;

[0014] The LED organic silicon encapsulation adhesive is formed by mixing component A and component B, wherein the mixing ratio of components A and B is: the molar ratio of the total amount of vinyl groups in components A and B to the total amount of silicon hydrogen groups is 1:(1.2-1.5);

[0015] The structural formula of the polyvinyl cyclosilane is shown in formula (I) or formula (II):

[0016]

[0017] Wherein, n=3-6, R1 is methyl, phenyl, isopropyl, C1-C 10 Ester group, epoxy group-containing C1-C 10 At least one of the alkyl groups; R2 is hydrogen, methyl, phenyl, isopropyl, C1-C 10 Ester group, epoxy group-containing C1-C 10 At least one of the alkyl groups; Vi is a vinyl group;

[0018] The structural formula of the silicon-hydrogen crosslinking agent is shown in formula (III):

[0019]

[0020] Wherein, R3, R4, R5, R6, and R7 are hydrogen, methyl, phenyl, isopropyl, C1-C 10 Ester group, epoxy group-containing C1-C 10 Alkyl, C1-C 10 At least one of the siloxane groups.

[0021] The LED organic silicon encapsulation adhesive component of the present invention uses a specific small molecule polyvinyl cyclosilane and a silicon-hydrogen crosslinking agent, wherein the number of silicon-oxygen bonds in the molecular structure of the polyvinyl cyclosilane is between 3 and 6, and the silicon-hydrogen crosslinking agent contains at least two silicon-hydrogen bonds. The advantages of using a small molecule basic adhesive system to replace the traditional polymer system are: the system has good fluidity, is easy to remove bubbles, has low viscosity, and does not have defects such as dispensing bubbles or wire drawing due to the high viscosity of the system; in addition, the active functional groups of the small molecules are more likely to participate in the curing reaction, and the curing is more thorough. The three-dimensional mesh pores of the silicone rubber formed after curing are denser and have a higher crosslinking density than the macromolecular polymer system, which can not only block the yellowing and aging caused by free radicals, but also improve the gas barrier properties of the material, and reduce the problems of material degumming or dead light caused by the erosion of water molecules and sulfur components in the air.

[0022] The present invention selects small molecule vinyl cyclosilane and hydrogen-containing silicone oil, which are easier to obtain certain special properties through modification. By designing the molecular structure of the small molecule silane of the base glue, the modified group can directly enter the vulcanized silica gel after curing, and solve the performance defects of the material from the substrate level. For example, the introduction of epoxy, ester, hydroxyl, carboxyl and other groups can improve the bonding performance without the need to add additional tackifiers, and can increase the light flux and high temperature and high humidity pass rate of the product; the introduction of fluorine elements can improve the gas barrier and surface stain resistance of the cured film, and improve the anti-sulfurization and high temperature and high humidity performance.

[0023] In addition, the introduction of ring bodies in the polyvinyl cyclosilane of the present invention reduces the slippage between molecules and improves the hardness and barrier properties of the product; the selected hydrogen-containing crosslinking agent has high reaction activity and fast curing reaction, which can greatly reduce the curing and baking process and improve efficiency. It does not require a complex synthesis process, is low-cost, pollution-free, and more environmentally friendly.

[0024] The total amount of vinyl and the total amount of silane groups in component A and component B of the present invention refer to the vinyl content and silane group content in all raw material components of the entire system of LED organic silicone encapsulation adhesive, and the vinyl content in the components is obtained by titration. When the molar ratio of the total amount of vinyl and the total amount of silane groups in component A and component B is selected to be 1: (1.2-1.5), it can be completely cured. By selecting specific types of small molecule polyvinyl cyclosilanes and silane crosslinkers and specific component ratios, the LED organic silicone encapsulation adhesive obtained has low viscosity, high crosslinking density, and good cold and hot shock performance, anti-vulcanization performance, barrier performance, heat resistance, and high temperature and high humidity performance.

[0025] Preferably, in the LED organic silicon encapsulant, the component A comprises the following components in parts by weight: 20-25 parts of polyvinyl cyclosilane and 0.004-0.006 parts of platinum catalyst;

[0026] The B component comprises the following components in parts by weight: 20-25 parts of a silane crosslinking agent and 0.1-0.5 parts of an inhibitor;

[0027] The mixing ratio of the A and B components is as follows: the molar ratio of the total amount of vinyl groups in the A and B components to the total amount of silane groups is 1:1.2.

[0028] When the preferred weight ratio is selected, the polyvinyl cyclosilane and the silicon hydrogen crosslinking agent can undergo a more complete curing reaction, so that the three-dimensional network structure formed by the obtained LED silicone encapsulation adhesive after curing is denser and has a higher crosslinking density, and the obtained material has better barrier properties and mechanical properties.

[0029] Preferably, in the LED organic silicon encapsulant, the component A further comprises the following components in parts by weight: 70-85 parts of a toughening agent; and the component B further comprises the following components in parts by weight: 50-75 parts of a reinforcing agent and 0-5 parts of a tackifier.

[0030] In the present invention, by adding a toughening agent to component A, the prepared encapsulating adhesive material can have better flexibility and high and low temperature performance, and by adding a certain amount of a reinforcing agent to component B, the strength performance of the encapsulating adhesive material is increased. At the same time, by adding a tackifier to component B, the bonding performance between the material and the LED lamp can be improved, water vapor erosion can be avoided, and the barrier performance can be improved.

[0031] Preferably, the toughening agent is 70-75 parts by weight; the reinforcing agent is 70-75 parts by weight, and the tackifier is 1-3 parts by weight.

[0032] Preferably, the toughening agent is vinyl-terminated phenyl silicone oil, the mass percentage of vinyl in the vinyl-terminated phenyl silicone oil is 1.1%-2.5%, and the viscosity is 50-500 mPa.s at 25°C.

[0033] Preferably, the reinforcing agent is a vinyl phenyl silicone resin, the mass percentage of vinyl in the vinyl phenyl silicone resin is 2.0-3.8%, the vinyl phenyl silicone resin is a solid resin or a liquid resin, and the viscosity of the liquid resin at 25°C is above 10000mPa.s. Solid resin refers to a vinyl phenyl silicone resin that is solid at room temperature (25°C). The number average molecular weight Mn of the solid resin selected in the present invention is between 500-2000. It is found through experiments that the number average molecular weight of the solid resin in the present invention has little effect on the performance of the obtained LED silicone encapsulation adhesive.

[0034] The vinyl-containing toughening agent and reinforcing agent added in the present invention can participate in the curing reaction, forming chemical bonds between the three-dimensional network system formed by curing the basic adhesive system, ensuring stable performance and avoiding the reduction of other properties after addition, and all properties can be maintained in good condition.

[0035] Preferably, the toughening agent is terminal vinyl phenyl silicone oil, the mass percentage of vinyl in the terminal vinyl phenyl silicone oil is 2.0%, and the viscosity is 300mPa.s at 25°C; the reinforcing agent is vinyl phenyl silicone resin, the mass percentage of vinyl in the vinyl phenyl silicone resin is 3.0-3.8%, the vinyl phenyl silicone resin is a solid resin or a liquid resin, the viscosity of the liquid resin at 25°C is 10000-30000mPa.s, and the number average molecular weight of the solid resin is 700-2000.

[0036] Preferably, the reinforcing agent is vinylphenyl MTQ silicone resin.

[0037] Preferably, the reinforcing agent is vinylphenyl MTQ solid silicone resin with a vinyl content of 3.5%.

[0038] Preferably, the polyvinyl cyclosilane is any one of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane, hexamethylhexavinylcyclohexasiloxane, 2,4,6-trimethyl-2,4,6-trivinylcyclotrisilazane and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasilazane.

[0039] Preferably, the silicon-hydrogen crosslinking agent is any one of phenyl tri(dimethylsiloxane)silane, tetramethyldiphenyl dihydrogen trisiloxane, and p-fluorophenyl tri(dimethylsiloxane)silane.

[0040] Preferably, the polyvinyl cyclosilane is any one of 2,4,6-trimethyl-2,4,6-trivinyl cyclotrisilazane and 1,3,5,7-tetramethyl-1,3,5,7-tetravinyl cyclotetrasilazane.

[0041] Preferably, the silicon-hydrogen crosslinking agent is phenyltri(dimethylsiloxane)silane.

[0042] When methyl polyvinyl cyclosiloxane and phenyl tri(dimethylsiloxane) silane are selected as the base adhesive raw materials, the obtained LED organic silicon encapsulation adhesive has a viscosity of less than 3000 mPa·s at 25° C. after component A and component B are mixed, a thermal shock failure rate of no more than 6%, an anti-vulcanization performance (luminous flux retention rate after vulcanization) of more than 75%, and excellent high-temperature aging performance and high-temperature and high-humidity performance.

[0043] Preferably, the refractive index of the platinum catalyst is 1.49-1.55.

[0044] Preferably, the refractive index of the vinyl phenyl-terminated silicone oil is 1.49-1.55;

[0045] Preferably, the refractive index of the vinyl phenyl silicone resin is 1.49-1.55.

[0046] Preferably, the inhibitor is any one of acetylenic compounds, vinyl siloxane, maleic acid and its derivatives, fumaric acid and its derivatives.

[0047] Preferably, the inhibitor is an alkynol compound.

[0048] Preferably, the inhibitor is 1-ethynylcyclohexanol.

[0049] Preferably, the tackifier is an organic silicon containing at least one of an ester group, an epoxy group, a boron group, and a vinyl group, the refractive index of the tackifier is 1.49-1.55, and the viscosity of the tackifier is 30-200 mPa.s at 25°C.

[0050] Preferably, the viscosity of the tackifier is 200 mPa.s at 25°C.

[0051] The refractive index of the platinum catalyst, toughening agent, reinforcing agent and tackifier selected in the present invention is between 1.49 and 1.55. Selecting components with similar refractive indexes can ensure that the final encapsulation adhesive has good light transmittance and meets the refractive index requirements.

[0052] In a second aspect, the present invention provides a method for preparing the above-mentioned LED silicone encapsulation adhesive, comprising the following steps:

[0053] Preparation of component A: Mix the materials of component A evenly to obtain component A;

[0054] Preparation of component B: uniformly mix the materials of component B to obtain component B;

[0055] The component A and the component B are mixed evenly in proportion to obtain the LED organic silicon encapsulation adhesive.

[0056] The preparation method of the present invention has simple process, does not require complicated synthesis, has low cost, is energy-saving and environmentally friendly, has improved production efficiency and high storage stability.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The present invention uses small molecule polyvinyl cyclosilane and silicon hydrogen crosslinking agent as the basic glue system to replace the traditional polymer system, which has good fluidity and low viscosity, avoiding the problems of dispensing bubbles or wire drawing caused by the high viscosity of the system. The three-dimensional network of silicone rubber formed after the small molecule system is cured is more compact and has a high crosslinking density. It can not only block the yellowing and aging caused by free radicals, but also improve the gas barrier performance of the material, and reduce the defects such as material degumming or dead light caused by the erosion of water molecules and sulfur components in the air. At the same time, the introduction of silane ring body reduces the slippage between molecules and improves the hardness and barrier properties of the product.

[0059] (2) The present invention can design the molecular structure of the small molecule silane base glue. After curing, the modified group can directly enter the vulcanized silica gel, thereby solving the performance defects of the material from the substrate surface. For example, the introduction of epoxy, ester, hydroxyl, carboxyl, etc. can improve the bonding performance without the need to add additional thickeners. This can avoid the problems of reduced transmittance and frost caused by precipitation caused by the additional addition of thickeners, thereby improving the luminous flux and high temperature and high humidity pass rate of the product; the introduction of fluorine element improves the heat resistance, anti-vulcanization performance and surface stain resistance of the encapsulation glue.

[0060] (3) The preparation method of the present invention has a simple process, does not require complex synthesis, has a fast curing reaction, reduces the curing process, saves energy and reduces consumption, has low cost, improves production efficiency, has high storage stability, and has broad application prospects. DETAILED DESCRIPTION

[0061] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.

[0062] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0063] Example 1

[0064] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0065] Component A contains the following ingredients by weight: 17 parts of trimethyl trivinyl cyclotrisiloxane, 83 parts of terminal vinyl phenyl toughening agent, and 0.004 parts of high-refractive platinum catalyst. The toughening agent of this embodiment was purchased from Anhui Aiyota Silicone Oil Co., Ltd., with a viscosity of 500mPa.s at 25°C, a refractive index of 1.49, and a vinyl content of 2.0%. The platinum catalyst is PT-2000, purchased from Guangzhou Siyou New Material Technology Co., Ltd.

[0066] Component B contains the following ingredients in parts by weight: 25 parts of phenyl tris (dimethylsiloxane) silane, 72 parts of vinyl phenyl MTQ resin (vinyl content 3.5%), 3 parts of V05 tackifier, and 0.1 parts of 1-ethynyl cyclohexanol inhibitor. The vinyl phenyl MTQ resin of this embodiment is purchased from Siwansi Materials Technology Nantong Co., Ltd., and is a solid powder with a number average molecular weight of 700 and a refractive index of 1.52. V05 tackifier is purchased from Jiangxi Lutai Technology Co., Ltd., and has a viscosity of 200 mPa.s at 25°C and a refractive index of 1.54.

[0067] In this embodiment, the component A and the component B are mixed and used in a molar ratio of the total amount of vinyl groups in the component A and the component B to the total amount of silane groups of 1:1.2.

[0068] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0069] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0070] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0071] The obtained A and B components are uniformly mixed in a mass ratio of 1:3 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.2) to obtain the LED organic silicon encapsulation adhesive.

[0072] Example 2

[0073] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0074] Component A comprises the following ingredients in parts by weight: 20 parts of pentamethylpentavinylcyclopentasiloxane, 80 parts of terminal vinylphenyl toughener (vinyl content 1.0%, viscosity 200mPa.s), and 0.004 parts of high-fold platinum catalyst.

[0075] Component B contains the following ingredients in parts by weight: 25 parts of tetramethyldiphenyldihydrotrisiloxane, 72 parts of vinylphenyl MTQ resin (vinyl content 3.8%, solid resin, number average molecular weight 950), 3 parts of V05 tackifier (viscosity 200mPa.s), and 0.4 parts of 1-ethynylcyclohexanol inhibitor.

[0076] In this embodiment, the component A and the component B are mixed and used in a molar ratio of the total amount of vinyl groups in the component A and the component B to the total amount of silane groups of 1:1.2.

[0077] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0078] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0079] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0080] The obtained A and B components are uniformly mixed in a mass ratio of 1:11 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.2) to obtain the LED organic silicon encapsulation adhesive.

[0081] Example 3

[0082] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0083] Component A comprises the following ingredients in parts by weight: 25 parts of 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasilazane, 75 parts of terminal vinylphenyl toughener (vinyl content 2.5%, viscosity 500mPa.s), and 0.006 parts of high-fold platinum catalyst.

[0084] Component B contains the following ingredients in parts by weight: 25 parts of phenyl tris(dimethylsiloxy)silane, 72 parts of vinyl phenyl MTQ resin (vinyl content 2%, viscosity 20000mPa.s), 3 parts of V05 tackifier (viscosity 200mPa.s), and 0.1 parts of 1-ethynyl cyclohexanol inhibitor.

[0085] In this embodiment, the components A and B are mixed and used in a molar ratio of the total amount of vinyl groups in the components A and B to the total amount of silane groups of 1:1.5.

[0086] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0087] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0088] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0089] The obtained A and B components are mixed evenly in a mass ratio of 1:4 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.5) to obtain the LED organic silicon encapsulation adhesive.

[0090] Example 4

[0091] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0092] Component A contains the following ingredients in parts by weight: 20 parts of 1,3,5-trimethyl-7-(2,3-epoxypropoxy)propyl-1,3,5,7-tetravinylcyclotetrasiloxane, 80 parts of terminal vinyl phenyl toughener (vinyl content 2.0%, viscosity 200mPa.s), and 0.004 parts of high-fold platinum catalyst.

[0093] Component B contains the following ingredients in parts by weight: 25 parts of phenyl tris(dimethylsiloxy)silane, 75 parts of vinyl phenyl MTQ resin (vinyl content 3.8%, solid MTQ resin, number average molecular weight of 1300), and 0.1 parts of 1-ethynyl cyclohexanol inhibitor.

[0094] In this embodiment, the component A and the component B are mixed and used in a molar ratio of the total amount of vinyl groups in the component A and the component B to the total amount of silane groups of 1:1.2.

[0095] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0096] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0097] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0098] The obtained A and B components are uniformly mixed in a mass ratio of 1:3 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.2) to obtain the LED organic silicon encapsulation adhesive.

[0099] Example 5

[0100] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0101] Component A contains the following ingredients in parts by weight: 18 parts of 1,3,5-trimethyl-7-acrylate-1,3,5,7-tetramethylcyclotetrasiloxane, 72 parts of terminal vinyl phenyl toughener (vinyl content 2%, viscosity 100mPa.s), and 0.004 parts of high-fold platinum catalyst.

[0102] Component B contains the following ingredients in parts by weight: 25 parts of p-fluorophenyl tris(dimethylsiloxy)silane, 75 parts of vinylphenyl MTQ resin (vinyl content 3%, solid MTQ resin, number average molecular weight of 2000), and 0.4 parts of 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane inhibitor.

[0103] In this embodiment, the component A and the component B are mixed and used in a molar ratio of the total amount of vinyl groups in the component A and the component B to the total amount of silane groups of 1:1.2.

[0104] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0105] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0106] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0107] The obtained A and B components are uniformly mixed in a mass ratio of 1:3 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.2) to obtain the LED organic silicon encapsulation adhesive.

[0108] Example 6

[0109] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0110] Component A comprises the following ingredients in parts by weight: 15 parts of trimethyltrivinylcyclotrisiloxane, 85 parts of terminal vinylphenyl toughener (vinyl content 2.0%, viscosity 100 mPa.s), and 0.0005 parts of high-fold platinum catalyst.

[0111] Component B contains the following ingredients in parts by weight: 20 parts of phenyl tris(dimethylsiloxy)silane, 50 parts of vinyl phenyl MTQ resin (vinyl content 3.8%, solid MTQ resin), 5 parts of V05 tackifier (viscosity 200 mPa.s), and 0.05 parts of 1-ethynyl cyclohexanol inhibitor.

[0112] In this embodiment, the components A and B are mixed and used in a molar ratio of the total amount of vinyl groups in the components A and B to the total amount of silane groups of 1:1.5.

[0113] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0114] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0115] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0116] The obtained A and B components are uniformly mixed in a mass ratio of 1:4.5 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.5) to obtain the LED organic silicon encapsulation adhesive.

[0117] Example 7

[0118] An embodiment of the LED organic silicon encapsulation adhesive of the present invention comprises component A and component B:

[0119] Component A comprises the following ingredients in parts by weight: 30 parts of trimethyltrivinylcyclotrisiloxane, 70 parts of terminal vinylphenyl toughener (vinyl content 2.0%, viscosity 500mPa.s), and 0.006 parts of high-fold platinum catalyst.

[0120] Component B contains the following ingredients in parts by weight: 50 parts of phenyl tris(dimethylsiloxane)silane, 48 parts of vinyl phenyl MTQ resin (vinyl content 2.5%, viscosity 25000mPa.s), 1 part of V05 tackifier (viscosity 200mPa.s), and 1 part of 1-ethynyl cyclohexanol inhibitor.

[0121] In this embodiment, the components A and B are mixed and used in a molar ratio of the total amount of vinyl groups in the components A and B to the total amount of silane groups of 1:1.5.

[0122] The preparation method of the LED organic silicon encapsulation adhesive described in this embodiment is as follows:

[0123] Prepare component A: weigh the above-mentioned component A materials according to proportion, and mix them evenly by oscillation or ultrasonic mixing to obtain component A.

[0124] Preparation of component B: weigh the above-mentioned component B materials according to proportion, and oscillate or ultrasonically mix to obtain component B.

[0125] The obtained A and B components are mixed evenly in a mass ratio of 1:1 (the molar ratio of the total amount of vinyl to the total amount of silicon-hydrogen bonds is 1:1.5) to obtain the LED organic silicon encapsulation adhesive.

[0126] The raw materials in Example 2-7 of the present invention: the terminal vinyl phenyl toughener and the vinyl phenyl MTQ resin are purchased from the same sources as in Example 1, except for the different vinyl content and parameter values. The platinum catalyst and the V05 tackifier in Example 2-7 are purchased from the same sources as in Example 1.

[0127] Comparative Example 1

[0128] The product of this comparative example is the imported Dow Corning OE-7662 product.

[0129] Comparative Example 2

[0130] The product of this comparative example is a domestic product of Dongguan Beiteli Company with model number BQ-4238.

[0131] Comparative Example 3

[0132] The product of this comparative example is KMT-1296 produced by Beijing Kangmeite Company.

[0133] Comparative Example 4

[0134] The product in this comparative example is the 9060T product imported from Debang.

[0135] Comparative Example 5

[0136] This comparative example provides an LED organic silicon encapsulation adhesive. The preparation method of the LED organic silicon encapsulation adhesive in this comparative example is the same as that in Example 1. The difference between this comparative example and Example 1 is that the component trimethyl trivinyl cyclotrisiloxane is replaced by vinyl silicone oil with a vinyl content of 3.1% and a viscosity of 4100 mPa.s. The vinyl silicone oil in this comparative example is a product of the PV-2 brand of Jiangxi Aoxiang New Materials Technology Co., Ltd.

[0137] Comparative Example 6

[0138] This comparative example provides an LED organic silicon encapsulation adhesive. The preparation method of the LED organic silicon encapsulation adhesive in this comparative example is the same as that in Example 1. The difference between this comparative example and Example 1 is that the component phenyl tris (dimethylsiloxane) silane is replaced by phenyl hydrogen silicone oil, the silane hydrogen content is 0.9%, and the viscosity is 700mPa.s. The phenyl hydrogen silicone oil in this comparative example is a PH-1 brand product purchased from Jiangxi Aoxiang New Material Technology Co., Ltd.

[0139] Comparative Examples 1-4 use domestic and imported samples with excellent performance on the market for comparison.

[0140] Performance Testing

[0141] The components A and B of the LED organic silicon encapsulation adhesive obtained in Examples 1-7 and the adhesive sample obtained in the comparative example were subjected to various performance tests.

[0142] Specific implementation steps: The A and B components obtained in Examples 1-7 are mixed evenly according to the ratio described in the examples, and the comparative ratio is mixed according to the product instructions; after mixing evenly, ultrasonic defoaming is performed, and then glue is dispensed on a 2835 bracket and a polytetrafluoroethylene mold with a diameter of 30 mm and a height of 2 mm, and then placed in an oven and baked at 100°C for 1h and 150°C for 3h to obtain a cured encapsulation glue.

[0143] The performance test methods for LED silicone encapsulation applications are as follows:

[0144] 1. Viscosity after mixing: After mixing A / B glue in proportion, use NDJ-5sS digital viscometer to test. The test temperature is 25℃. Each sample is tested 3 times to get the average value.

[0145] 2. Shore hardness: After mixing A / B glue in proportion and baking and curing, use Shore D durometer to test the hardness.

[0146] 3. Transmittance: Mix A / B glue in proportion, bake and solidify into a disc with a diameter of 30mm and a height of 2mm. Use a UV-visible light photometer to test the transmittance of the disc at a wavelength of 400nm.

[0147] 4. Refractive index: Tested using an Abbe refractometer.

[0148] 5. Anti-sulfurization: Place 0.5g of dry sublimated sulfur powder in a 1000mL glass container, and use sulfur-free tape to stick the packaged LED lamp beads into it, then place it in an oven at 105℃±2℃ for 2h and take it out to test the average luminous flux retention rate of the lamp beads before and after sulfurization.

[0149] 6. Hot and cold shock: Place the packaged LED lamp beads in a high and low temperature box, set the conditions to -40℃, 30min-30s-100℃, 30min, and test 200 cycles to see if there are any defective rates such as discoloration, cracking, leakage and dead light.

[0150] 7. Red ink: Immerse the packaged LED lamp beads in red ink (red ink: pure water = 1:1), place them on a heating platform at 120℃ for 2 hours, and observe the red ink penetration rate.

[0151] 8. High temperature aging: Place the cured sample in an oven at 250°C for 24 hours and visually observe the degree of yellowing.

[0152] 9. High temperature and high humidity: Under 85℃ / 85RH environment, after the lamp is continuously lit for 168h at 1.2 times the rated current, there will be defects such as discoloration, cracking, leakage and dead light.

[0153] 10. Surface stain resistance: Place the cured wafer sample outdoors for 1000 hours and observe the surface contamination.

[0154] The performance test results of the LED silicone encapsulants described in Examples 1-7 and the samples obtained in Comparative Examples 1-6 are shown in Tables 1 and 2.

[0155] Table 1

[0156]

[0157]

[0158] Table 2

[0159]

[0160]

[0161] As shown in Table 1 and Table 2, the viscosity of the LED organic silicon encapsulation glue obtained in Examples 1-7 after mixing is significantly lower than that of the comparative example product, while the hardness is improved, and the cold and hot shock, anti-sulfurization performance, high temperature anti-yellowing performance and high temperature and high humidity performance are all better than the comparative example. The viscosity of the LED organic silicon encapsulation glue obtained in Comparative Examples 1-6 at 25°C after mixing in proportion is greater than 3000mPa.s, which is easy to cause dispensing bubbles and drawing; at the same time, the cold and hot shock defect rate and the high temperature and high humidity defect rate are increased, and the anti-sulfurization performance is reduced.

[0162] In Example 4, epoxy groups are introduced into the main chain of the vinyl base adhesive for modification, which increases the adhesion between the cured resin and the substrate. Without the addition of an additional tackifier, it still has very excellent adhesion, good barrier properties, and is not invaded by moisture, which can avoid the decrease in light transmittance and the frost spraying caused by the addition of vinyl phenyl silicone resin and tackifier. In Example 5, fluorine atoms are introduced into the silicon hydrogen crosslinking agent, which significantly improves the heat resistance, barrier properties and surface stain resistance of the encapsulation adhesive, and at the same time, the anti-sulfurization performance is improved.

[0163] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An LED silicone encapsulation adhesive, characterized in that: The method comprises the following components: component A and component B, wherein component A comprises the following components in parts by weight: 15-30 parts of polyvinyl cyclosilane and 0.0005-0.006 parts of platinum catalyst; The B component comprises the following components in parts by weight: 20-50 parts of a silane crosslinking agent and 0.05-1 part of an inhibitor; The LED organic silicon encapsulation adhesive is formed by mixing component A and component B, wherein the mixing ratio of components A and B is: the molar ratio of the total amount of vinyl groups in components A and B to the total amount of silicon hydrogen groups is 1:(1.2-1.5); The structural formula of the polyvinyl cyclosilane is shown in formula (I) or formula (II): Wherein, n=3-6, R1 is methyl, phenyl, isopropyl, C1-C 10 Ester group, epoxy group-containing C1-C 10 At least one of the alkyl groups; R2 is hydrogen, methyl, phenyl, isopropyl, C1-C 10 Ester group, epoxy group-containing C1-C 10 At least one of the alkyl groups; Vi is a vinyl group; The structural formula of the silicon-hydrogen crosslinking agent is shown in formula (III): Wherein, R3, R4, R5, R6, and R7 are hydrogen, methyl, phenyl, isopropyl, C1-C 10 Ester group, epoxy group-containing C1-C 10 Alkyl, C1-C 10 At least one of siloxane groups; The A component further comprises the following components in parts by weight: 70-85 parts of a toughening agent; the B component further comprises the following components in parts by weight: 50-75 parts of a reinforcing agent and 0-5 parts of a tackifier; The toughening agent is a terminal vinyl phenyl silicone oil, the mass percentage of vinyl in the terminal vinyl phenyl silicone oil is 1.1%-2.5%, and the viscosity at 25°C is 50-500mPa.s; the reinforcing agent is a vinyl phenyl silicone resin, the mass percentage of vinyl in the vinyl phenyl silicone resin is 2.0-3.8%, and the vinyl phenyl silicone resin is a solid resin or a liquid resin, and the viscosity of the liquid resin at 25°C is above 10000mPa.s; The silicon-hydrogen crosslinking agent is any one of phenyl tri(dimethylsiloxane)silane, tetramethyl diphenyl dihydrogen trisiloxane, and p-fluorophenyl tri(dimethylsiloxane)silane.

2. The LED silicone encapsulant according to claim 1, characterized in that: The component A comprises the following components in parts by weight: 20-25 parts of polyvinyl cyclosilane and 0.004-0.006 parts of platinum catalyst; The B component comprises the following components in parts by weight: 20-25 parts of a silane crosslinking agent and 0.1-0.5 parts of an inhibitor; The mixing ratio of the A and B components is as follows: the molar ratio of the total amount of vinyl groups in the A and B components to the total amount of silane groups is 1:1.

2.

3. The LED silicone encapsulant according to claim 1, characterized in that: The toughening agent is 70-75 parts by weight; the reinforcing agent is 70-75 parts by weight, and the tackifier is 1-3 parts by weight.

4. The LED silicone encapsulant according to any one of claims 1 to 3, characterized in that: The polyvinyl cyclosilane is any one of 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, pentamethylpentavinylcyclopentasiloxane, hexamethylhexavinylcyclohexasiloxane, 2,4,6-trimethyl-2,4,6-trivinylcyclotrisilazane and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasilazane.

5. The LED silicone encapsulant according to any one of claims 1 to 3, characterized in that: The refractive index of the platinum catalyst is 1.49-1.

55.

6. The LED silicone encapsulant according to claim 1, characterized in that: The refractive index of the terminal vinyl phenyl silicone oil is 1.49-1.55; the refractive index of the vinyl phenyl silicone resin is 1.49-1.55; the tackifier is an organic silicone containing at least one of an ester group, an epoxy group, a boron group, and a vinyl group; the refractive index of the tackifier is 1.49-1.55, and the viscosity of the tackifier is 30-200 mPa.s at 25°C; the inhibitor is any one of an acetylene compound and a vinyl siloxane.

7. The method for preparing the LED organic silicon encapsulant according to any one of claims 1 to 6, characterized in that: The steps include: Preparation of component A: Mix the materials of component A evenly to obtain component A; Preparation of component B: uniformly mix the materials of component B to obtain component B; The component A and the component B are mixed evenly in proportion to obtain the LED organic silicon encapsulation adhesive.

Citation Information

Patent Citations

  • Cyclic siloxane composition, method for producing the same, and use of the same

    JP2015155521A